Literature Review: Adolescent Perceptions Toward Teenage Pregnancy - Delia Amalia; Ermiati Ermiati; Eka Afrima Sari (Journal of Nursing Science Update (JNSU), 2021)
Teenage pregnancy is one of the health problems in developing countries that has not been resolving yet. Adolescent perception is one of the factors that influence the incident of teenage pregnancy. At present, there are still limited research articles about adolescent perceptions toward teenage pregnancy. The purpose of this literature study is to find out how adolescent perceptions toward teenage pregnancy. This literature study used a scoping review method. There were 6 articles was analyzed after sorting by inclusion criteria consisting of the article contained an explanation or description of adolescent perceptions of teenage pregnancy, the year 2015-2020, English or Indonesian, full text, samples aged 10-19 years. The result of the study found out that adolescents had negative perceptions such as pregnancy among adolescents is too young, teenage pregnancy caused by several factors, and has various negative impacts toward adolescents, parents, and infants. Furthermore, adolescents had positive perceptions such as teenage pregnancy in adolescent is normal, life will not differ, her boyfriend will be responsible to her pregnancy. The conclusions from this literature review were the difference in perceptions between adolescents towards pregnancy in adolescents is influenced by adolescent environmental culture and believed.